Author's integrity to be preserved - The Sun, Husna Yusop (2011)
PUTRAJAYA:The independent panel to look into amending the Interlok novel,which met for the first time yesterday,has agreed that the integrity of the author,national laureate Datuk Abdullah Hussain,shold be preserved.